Accepted Safe Food‐Handling Procedures Minimizes Microbial Contamination of Home‐Prepared Blenderized Tube‐Feeding. (29th January 2020) - Milton, Debra L.; Johnson, Teresa W.; Johnson, Kelly; Murphy, Brie; Carter, Holly; Hurt, Ryan T.; Mundi, Manpreet S.; Epp, Lisa; Spurlock, Amy Y.; Hussey, Jenna
Abstract: Background: The number of patients requiring home enteral nutrition (HEN) continues to increase. Many of these patients are interested in using blended food instead of, or in addition to, commercial enteral formula (CEF). Increased risk of food‐borne illness is a concern of blenderized tube‐feeding (BTF). This project assessed a standard procedure for minimizing bacterial growth of BTF prepared in the home setting. Methods: Fifty participants prepared BTF in their kitchens using a standard preparation procedure to minimize bacterial contamination. BTF was assessed for growth of aerobic microorganisms, Escherichia coli, Staphylococcus aureus, and coliforms at baseline, 24‐hour, and 48‐hour intervals after preparation for a total of 150 colony forming units (CFU) counts performed. Results: No sample had zero aerobic microbial counts; yet no substantial increase in microbial counts was observed during the 48 hours. At baseline and 24 hours, 5/50 (10%) had a CFU count of >10 4, and at 48 hours, 6/50 (12%) exceeded 10 4 CFUs. Out of 150 CFU counts, 2 (1.3%) were just over 10 5 CFU/mL. Samples exceeding 10 4 CFU/mL were likely contaminated by common endospore‐forming bacteria found in soil or by bacteria in milk that was close to its expiration date. Conclusion: In this study, 88% of the samples met the US Food Code criteria for safe food consumption; 10.7% met guidelines for marginal safety by other standards; and 1.3% slightly exceeded 10 5 CFUs. Established safe food‐handling procedures can minimize bacterial contamination of BTF and consequently reduce risk of food‐borne infection in HEN patients.